VISÕES DO ORIENTE EM EÇA DE QUEIRÓS: uma análise comparatista entre os Relatos de viagem e A relíquia - Ghignath, Rosana Carvalho da Silva (2008)
This dissertation has as objective to study, in comparative perspective , the works of Eça de Queirós the "trip" Reports - Egypt, Palestine and High Syria -, everybody published posthumously, and the novel The Relic, published in the author's life. It fits to illuminate that the Portuguese novelist undertook a trip to the East, specifically to Egypt and Palestine, in the middle of 1869, motivated by the inauguration of the Channel of Suez. The annotations done by Eça concerning the places that he knew, in odds papers, they were published firstly by its son José Maria d´ Eça de Queiroz, fifty seven years then, entitling them as Egypto. Trip notes (1926). In 1966, the novelist's daughter, Maria Eça de Queiroz de Castro, picked up more notes of this material, composing the book Free Leaves, of which they make part the reports on Palestine and on Syria. In these works they are the author's personal impressions in relation to the that he saw in those distant places paragens. The Relic is already work ficcional published in 1887. In this novel, the narrator-character's trip, Teodorico Raposo, is shown by the Medium East. When doing an comparative analysis among these written, it is noticed that the novelist took advantage of its oriental course to redraft fiction, journalistic and epistle texts. Starting from the reading of the " Reports of Trip " and d´A relic, this dissertation seeks to investigate mapear the eatern imaginary in the works queirosianas, aiming the novelist's insert in the context of the easstern European century XVIII, as well as the influences that the writer received from the main works of French artists that also traveled to the East, to example of Flaubert, Renan and Gautier. He makes himself a literary analysis still comparing the texts of the "Reports of trip" writings for Eça young with the novel The relic, written in the writer's full maturity. They guide this study the theories of the parody, of the intratextualidade and of the irony as structures of the satirical and revision speech, that, it is believed, according to this novel of Eça de Queirós.